Aplikasi Algoritma Simulated Annealing untuk Pemodelan Fluktuasi Temperatur di Lapisan Tropopause - Dasep Dasep; Noersomadi Noersomadi; Rizkia Putri Syafina (Universitas Pendidikan Indonesia (UPI), 2023)
Atmospheric conditions influence various sectors of human activity, so it is important to study the dynamics of the atmospheric layers, especially those related to temperature fluctuations. The aim of this research is to investigate the model of temperature fluctuations in the tropopause layer (at an altitude of 17 km) by determining the wave amplitude and phase parameters. The method for obtaining parameters is defined as simulated annealing inversion, which is a simulation of finding solutions at global critical points. The data used in this study are temperature at 17 km, which retrieved from the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) Mission #2 GNSS radio occultation satellite during April–May 2021. The results of the annealing simulation show that the amplitude and phase parameters of atmospheric waves in the tropopause layers vary between 3.4–23.86 K and 7.3–52.5°, respectively. The simulation model shows that the temperature spreads from west to east and fluctuates between –25 and 25 K.Keywords: Atmospheric Waves, Simulated Annealing, Temperature, Tropopause Layer. AbstrakKondisi atmosfer mempengaruhi berbagai sektor kegiatan manusia, sehingga studi tentang dinamika di lapisan atmosfer penting dilakukan terutama terkait dengan fluktuasi temperatur. Tujuan dari penelitian ini memodelkan fluktuasi temperatur di lapisan tropopause (ketinggian 17 km) dengan mencari nilai parameter amplitudo dan fasa gelombang yang mendekati data pengamatan. Metode pencarian parameter tersebut adalah inversi simulated annealing, yaitu simulasi pencarian solusi pada titik kritis global. Data penelitian ini adalah variabel temperatur di 17 km yang bersumber dari pengamatan satelit Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) Mission #2 GNSS radio occultation selama periode April-Mei 2021. Hasil simulasi annealing menunjukkan parameter amplitudo dan fasa gelombang atmosfer di lapisan tropopause berturut-turut bervariasi pada rentang 3,4–23,86 K dan 7,3°–52,5°. Model simulasi menunjukkan perambatan temperatur dari arah barat ke timur dan berfluktuasi pada selang –25 sampai 25 K.